Developing industrial technology : lessons for policy and practice - Najmabadi, Farrokh; Lall, Sanjaya (Washington, D.C. : World Bank, 1995)
This book by the Bank's Operations Evaluation Department assesses how the Bank's lending for industrial technology has affected industry in six countries: India, Indonesia, Hungary, Korea, Mexico, and Spain. Based on experience with projects in contrasting economic settings, the study assesses the determinants of industrial technology development and the suitability of government policies.
Preface and summary in French and Spanish.
Includes bibliographical references.
gau 02/11/2016
Loans
Keywords: Appropriate technology; Sustainable development; Industrialization; Industrial development projects; Industrial policy